The Effectiveness of Exercise Therapy on Reducing Pain in Osteoarthritis Patients: Literature Review - Warsono Warsono (Universitas Muhammadiyah Semarang, 2020)
Osteoarthritis (OA) is a chronic joint disorder with damage to the joint cartilage, this causes a decrease in the functional ability and perform daily activities. So intervention is needed in reducing these problems to increase and maintain independence in carrying out training activities. The research will aim to detect the influences of exercises that can be applied to OA patients to reduce pain. This research used a systematic literature study approach obtained from PubMed database and Science Direct. In total, the literature review systematic review concluded that exercise therapy can affect pain in osteoarthritis. The results of this systematic review revealed that yoga improves OA symptoms and can be done safely without supervision at home. In conclusion, the result of this study showed that there were Moderate physical activity at least three times per week can reduce the risk of arthritis-related disability. However, there is increasing evidence in the literature for the beneficial effects of exercise for managing OA. Evidence on the comparative effectiveness of different types of exercise, including exercise adherence and satisfaction in older adults with knee OA, is limited.